Dicer affects cisplatin-mediated apoptosis in epithelial ovarian cancer cells - Wang, Xi (Mol Med Rep, 2018)
Dicer is an essential enzyme that processes micro (mi)-RNA precursors into mature miRNAs, and serves a critical role in cancer development and progression by regulating gene expression. However, the role of Dicer in cisplatin-mediated apoptosis and chemotherapy resistance in epithelial ovarian cancer (EOC) cells is poorly understood. In the present study, Dicer was expressed at low levels in cisplatin-resistant A2780 cells when compared with parental cells. In addition, knocking down Dicer using short hairpin RNA decreased the sensitivity of A2780 and CAOV3 cells to cisplatin. Furthermore, downregulating Dicer significantly inhibited cisplatin-induced apoptosis in ovarian cancer cells, and decreased the levels of proteins involved in apoptosis signaling pathways, including P73, P63, P53, caspase-9 and caspase-3. These findings indicated that Dicer may be a promising target for overcoming drug resistance in ovarian cancer.